Contribution of Non-Governmental Organizations on Poverty Reduction in Kabale District: A Case study of Buhara Sub-County. - Adebayo, Sanni T. (International Research Journals, 2018)
This study is set out to investigate the contribution of non governmental organizations on poverty reduction in Kabale District: A case study of Buhara Sub-county. The sample population is both males and females of Buhara Sub-county in all the parishes. The researcher employed survey methods based on questionnaire method of data collection. The questionnaire was administered to beneficiaries and non -beneficiaries both males and females of Buhara Sub-county in all the parishes. Focus group discussions also employed, the researcher interview key informants like LCs youth representatives, women representatives, church leaders and extension workers in Buhara Sub-county. The research questions focused on what is the contribution of NGOs on poverty reduction in Buhara Sub-county; what are the major causes of poverty in Buhara Sub-county; what are the indicators of poverty in Buhara Sub County; what are the possible solutions to the identified causes of poverty?. The findings of the study are on the contribution of non governmental organizations on poverty reduction. The study established that the interventionists NGO’s are to perceive the communities in self- help development project to reduce the poverty. It is when this notion is firmly rooted in them that they can use their interventions in form of technical, financial and material aids to stimulate the benefiting communities to participate actively in promotion of poverty reduction in the district. This study is try to assess the contribution of non governmental organization in poverty reduction in Buhara of Kabale.